The Effect of PSB in Soil and Biochar Planting Media on the Growth of Water Spinach Plants - Sa'diyah, Halimatus; mutiati, enni (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2024)
Water spinach is one type of vegetable that is liked by the public, because it has a delicious taste and high nutritional content, so the productivity of water spinach plants is getting higher every year. In dealing with the problems that occur, efforts are needed to improve the process of planting kale, both in terms of the planting media used, the addition of fertilizer, good planting procedures, and so on. The aim of this research was to determine the effect of PSB in soil and biochar planting media on the growth of water spinach plants. The method used in this research was a factorial randomized block design consisting of 2 factors and 3 replications, namely factor 1 PSB fertilizer and factor 2 soil and bichar planting media, so that there were 2 combinations with 15 treatments. The results of the research show that PSB can influence soil and biochar planting media on the growth of kale plants. Very good growth of kale plants was found in polybags with the addition of PSB with a concentration of 20%, while in other polybags almost showed the same growth. The conclusion from the research that has been carried out is that PSB can have an effect on soil and biochar planting media on the growth of kale plants, which can be seen by the fact that the growth process of kale plants is faster and the results of kale plants are fresher.